Tinjauan Produksi Daerah Penghasil Kelapa Sawit di Sumatera Barat dengan Analisis Profil - Inshanul Fadhila; Helma Helma (Journal of Mathematics UNP, 2023)
Palm oil is an important industrial plant and has a benefits of palm oil as the main raw material for cooking oil, increasing the country's foreign exchange and as a mainstay commodity of non-oil and gas exports. West Sumatra has 19 regencies and cities, but only 14 regencies and cities that produce palm oil. There is a high inequality in average productivity, so it is necessary to describe the ideal production of productive land area and oil palm production in West Sumatera using profile analysis. This study aims to determine the results of profile analysis in districts/cities in West Sumatra that produce palm oil. The results are the comparison of production and ideal production of the average land area in West Sumatra is not the same. There are three types of regions based on the level of optimization as follows: (1) non-optimal areas, namely West Pasaman Regency,  Sijunjung, Agam, Pesisir Selatan, Pasaman, and Dharmasraya Regencies (2) almost optimal areas, namely Lima Puluh Kota Regency. (3) optimal areas are Solok Regency, Padang Pariaman, South Solok, Padang City, Solok City, Sawahlunto City, and Pariaman City.